CAMPUR KODE LIRIK LAGU JKT48 - Geta, Bertolomeus; Meidariani, Ni Wayan; Andriyani, Anak Agung Dian (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2022)
This article analyzes the use of code mixing in JKT48 song lyrics. The purpose of writing is to determine the types and forms of code mixing. This thesis uses Nababan's social linguistic theory in Padmadewi (2014). Sources of data studied in this study using primary data. The method used in this research is a qualitative method with an interpretive descriptive research type. And the data collection technique in this article uses the listening method, with note-taking techniques, and classification. While the method of presenting the results of data analysis using descriptive methods and qualitative techniques. The results of data analysis using informal methods. The types of code mixing found in the data are exit code mixing and code mixing forms found in the data, namely code mixing in the form of words, code mixing in the form of phrases, and code mixing in the form of sentences. The results of the data analysis of this study were 15 types of exit code mixing, 13 data word code mixing forms, 1 data code phrase mix form, and 1 data code sentence mix form.